The Role of Hydrocolonic Sonography in Diagnostics of the Intussusceptions due to Neoplastic Process in Children - M Yu. Yanitskaya; I. A. Turabov (Креативная хирургия и онкология)
Introduction. A nonsurgical reduction is the treatment of choice for intestinal intussusception. A neoplasm-associated intussusception always requires surgery. In case of a tumour it is very important to have the diagnosis determined prior to surgical treatment. The hydrocolonic sonography technique makes it possible to assess the tissue structure and to visualize the lumen of the intestine.Materials and methods. The study presents a retrospective comparative analysis of clinical manifestations and diagnosis methods in all the patients with intussusception (n = 380) treated at the Arkhangelsk Children’sClinicalHospital in 1981–2018. This included all the neoplasm-associated intussusception cases (tumours and polyps). The data was compared to clinical manifestations of intussusception associated with other causes (idiopathic, mesenteric node hyperplasia, diverticulum).Results. Neoplasm-associated intussusception is a rare occurrence (2.3%). If the cause of the intussusception is a tumour the typical recorded manifestations include the combination of the signs of gastrointestinal diseases and loss of weight (8–12%), and a chronic course of development (over one to three months). Polyp-associated small intestinal and ileocolic intussusception, a casuistically rare situation, first manifested as an acute intestinal obstruction with protracted abdominal pain syndrome in anamnesis, or recurrent intussusceptions. Traditional and hydrocolonic sonography made it possible to make the diagnosis of intussusception and to identify a tumour. Non-tumour-associated intussusception presented with an acute course of the disease in every case. It manifested with the typical triad of symptoms (abdominal colic pain, rectal haemorrhage, palpable intussusceptum mass) in every third case. The manifestation of the disease as the dyad of symptoms (vomiting and abdominal colic pain) was significantly more frequent (p = 0.001).Conclusions. Clinical presentation of neoplasm-associated intussusception has certain unique qualities. The ultrasound of abdominal cavity and hydrocolonic sonography make it possible to find the intussusception and to identify the tumour or polyp in the structure of the intussusceptum in 100 % of cases at primary examination. The data obtained is used for the optimisation of the surgical treatment strategy.